Exploring the Critical Components and Therapeutic Mechanisms of Perilla frutescens L. in the Treatment of Chronic Kidney Disease via Network Pharmacology - Yong, Chen; Zhang, Zhengchun; Huang, Guoshun; Yang, Yang; Zhu, Yiye; Qian, Leilei; Tian, Fang; Liu, Li; Wu, Qijing; Xu, Zhongchi; Chen, Chong; Zhao, Jing; et al. (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is a chronic progressive disease that seriously threatens human health. Some patients will continue to progress into the CKD stage 3-5 (also called chronic renal failure), which is mainly manifested by a decline in renal function and multi-system damage. Perilla frutescens (L.) Britton. (Lamiaceae) is one of the most widely used traditional Chinese medicine (TCM) herbs in CKD, especially in CKD stage 3-5. But its active components and mechanisms are still unclear. In this study, we used network pharmacology to analyze the active components of P. frutescens and the main therapeutic targets for intervention in CKD stage 3-5. Then, the key components were selected for enrichment analysis and identified by high performance liquid chromatograph (HPLC). Finally, we verified the critical components through molecular docking, and in vitro experiments. The results show that 19 main active components of P. frutescens were screened, and 108 targets were intersected with CKD stage 3-5. The PPI network was constructed and found that the core nodes AKT1, TP53, IL6, TNF, and MAPK1 may be key therapeutic targets. Enrichment analysis shows that related targets may be involved in regulating various biological functions, and play a therapeutic role in CKD stage 3-5 by regulating apoptosis, T cell receptor, and PI3K-AKT signaling pathways. Molecular docking indicates that the key active components were well docked with its corresponding targets. Five active components were identified and quantified by HPLC. According to the results, luteolin was selected as the critical component for further verification. In vitro experiments have shown that luteolin can effectively alleviate adriamycin (ADR)-induced renal tubular apoptosis and suppress AKT and p53 phosphorylation. The effects of luteolin to reduce apoptosis may be mediated by inhibiting oxidative stress and downregulating the mitogen-activated protein kinase (MAPK) and p53 pathways. In general, we screened and analyzed the possible active components, therapeutic targets and pathways of P. frutescens for treating CKD. Our findings revealed that luteolin can reduce renal tubular epithelial cell apoptosis and may be the critical component of P. frutescens in the treatment of CKD. It provides references and direction for further research.